2017
DOI: 10.5004/dwt.2017.20369
|View full text |Cite
|
Sign up to set email alerts
|

Coating of reverse osmosis membranes with amphiphilic copolymers for biofouling control

Abstract: a b s t r a c tSurface coating of membranes may be a promising option to control biofilm development and biofouling impact on membrane performance of spiral-wound reverse osmosis (RO) systems. The objective of this study was to investigate the impact of an amphiphilic copolymer coating on biofilm formation and biofouling control. The coating was composed of both hydrophilic and hydrophobic monomers hydroxyethyl methacrylate (HEMA) and perfluorodecyl acrylate (PFA), respectively. Commercial RO membranes were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Antai et al [173][174][175][176][177][178][179][180][181][182][183][184][185][186][187] ) within GO was done via three different methods such as Pre-incorporation, Post-incorporation and Filter-incorporation. Metal cations used for membrane preparation used were non-toxic, environment friendly and cheap [188][189][190][191][192][193][194].…”
Section: Role Of Graphene Oxide In Polymer Nano-composite Membranesmentioning
confidence: 99%
“…Antai et al [173][174][175][176][177][178][179][180][181][182][183][184][185][186][187] ) within GO was done via three different methods such as Pre-incorporation, Post-incorporation and Filter-incorporation. Metal cations used for membrane preparation used were non-toxic, environment friendly and cheap [188][189][190][191][192][193][194].…”
Section: Role Of Graphene Oxide In Polymer Nano-composite Membranesmentioning
confidence: 99%
“…Therefore, long-term studies (i.e., several months) are needed to investigate the effective impact of membrane surface modification on biofouling development. It has also been shown experimentally that long-term biofouling studies are more representative for practice than short-term protein and bacterial adhesion tests (Bucs et al, 2017;Louie et al, 2011;Miller et al, 2012).…”
Section: Membrane Modificationmentioning
confidence: 99%
“…Few studies investigating coated membranes to control fouling reported on the coating stability (Brzozowska et al, 2011;Bucs et al, 2017;Louie et al, 2006;Ronen et al, 2015). Brzozowska et al (2011) reported a weak attachment of polymer brushes to the membrane surface, with the coating layer easily removed by the water flow.…”
Section: Membrane Modificationmentioning
confidence: 99%
“…Such device should be representative for conventionally used membrane modules, thus involving the used materials (properties and structure) such as membrane and spacer, the height of the flow channels and hydraulics. The membrane fouling simulator (MFS) was introduced in 2006 [4] and since then many articles have appeared on various research aspects of biofilm characterization [2,3,[27][28][29][30][31][32][33][34][35][36], biofouling control [5,[37][38][39][40][41][42][43][44][45][46][47][48][49], and strategies for early warning of biofouling [50][51][52][53][54][55] applying the developed MFS.…”
Section: Lh Kim Et Al / Desalination and Water Treatment 126 (2018mentioning
confidence: 99%
“…Feed spacers have been shown to have a strong impact on biofouling [46]. MFS studies have been performed to evaluate feed spacers (i) as applied in practice, including varying spacer thickness [37], (ii) after modifications by hydrophilic, amphiphilic bactericidal and biocidal coatings [38,39,42], and with innovative geometries [29,44,48,86,87]. A novel strategy for a cost-effective development and evaluation of feed spacers was developed for biofouling and scaling control involving (i) numerical modeling, (ii) three-dimensional (3D) printing of spacers, and (iii) MFS testing of hydrodynamics and biofouling impact [43].…”
Section: Impact Of Feed Spacer Geometrymentioning
confidence: 99%